Innervation Relationships of the Gallbladder Nerve Apparatus with Spinal and Rheumatic Nerve Ganglia (Literature Review) (Eurasian Medical Research Periodical, 2023)
The biliary system is characterized by the presence of many sphincters, the coordinated work of which results in bile excretion into the intestine at the moment of digestion and into the gallbladder outside the moment of digestion. It has been established that there is a direct innervation connection between them. In addition, the gallbladder has innervation connections with other organs of the abdominal cavity. Therefore, in diseases of the gallbladder there are concomitant disorders of functions of other organs and clarification of the nervous mechanism of these concomitant reactions has a certain importance.